Viscoelastic Capillary Flow Cytometry. Issue 2 (23rd December 2022) - Serhatlioglu, Murat; Jensen, Emil Alstrup; Niora, Maria; Hansen, Anne Todsen; Nielsen, Christian Friberg; Jansman, Michelle Maria Theresia; Hosta-Rigau, Leticia; Dziegiel, Morten Hanefeld; Berg-Sørensen, Kirstine; Hickson, Ian David; Kristensen, Anders
Abstract : A compact microfluidic flow cytometer is demonstrated, comprising viscoelastic flow focusing in fused silica capillaries and a fiber optical interface. Viscoelastic flow focusing enables simple device design and operation with a single‐inlet/outlet fluidic configuration. Fused silica capillaries with different inner diameters are effortlessly interchanged to eliminate blockage ratio limitations and enable single‐train particle focusing for a wide range of particle sizes and geometries. The compact system is mounted on an inverted microscope for easy integration with optical imaging and other optofluidic modalities, such as optical trapping and particle sorting. A real‐time cytometric analysis of three channels, forward scattering, side scattering, and fluorescence detection, is performed on LABVIEW. A throughput of 3500 events s −1 is performed on particles of sizes ranging from 2 to 20 μm, using capillaries of different inner diameters ranging from 30 to 75 μm. The outer diameter of all capillaries is identical to the cladding diameter of the applied optical fibers. This enables easy exchange and precise optical alignment of fibers and capillaries on a microfabricated jig. The performance of the microfluidic flow cytometer is benchmarked using polystyrene calibration beads, poly(lactic ‐co ‐glycolic acid) particles, erythrocytes, THP‐1 leukemic monocytes, and human metaphase chromosomes. Abstract : A compact microfluidic flow cytometer (MFC) comprising viscoelastic flow focusing fused silica capillaries and a fiber optical interface is presented. The MFC is mounted on an inverted microscope for easy integration with other optofluidic modalities. Viscoelastic MFC with a throughput of 3500 events s −1 is performed on various type of particles, with sizes ranging from 2 to 20 μm.